Adaptasi Mahad Aly Al Hasaniyah Sendang Senori Tuban Dalam Menghadapi Era Revolusi Industri 4.0 - Mafiyah Tukhfatun Nafi; Ahmad Suyanto (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2022)
The curriculum is the most important thing in the educational process. This study aims to examine the adaptation of salaf pesantren to era 4.0 with the presence of Mahad Aly in changes in curriculum management. The research method used by the researcher is descriptive qualitative with a field research approach. Sources of data in this study obtained from observations, interviews, and documentation. The results of the study show that: (1) Understanding Salaf Islamic Boarding Schools and Era 4.0. (2) The management of the Mahad Aly Al Hasaniyah curriculum entering the 4.0 era has three stages, namely: (a) Mahad Aly Al Hasaniyah curriculum planningentering 4.0 era three stages, namely the computer skills program, the preparation of the lesson schedule. (b) Implementation of the Mahad Aly Al Hasaniyah curriculum entering the 4.0 era, namely the implementation of daily learning, the implementation of computer skills twice a week, the use of streaming media in an activity, the use of E-book references (maktabah syamilah), and dawah skills through various media. (c) Evaluation of the Mahad Aly Al Hasaniyah curriculum entering this 4.0 era, namely applying the sorogan method, observing student activity in class, Mid-Semester Examination (UTS), Final Semester Examination (UAS), Making minutes and observing activities.